EPU of China and investment opportunities: A tale of Asean stock markets - Mohd Thas Thaker, Hassanudin *; Mohd Thas Thaker, M. A.; Muhammad Rizky, P. S.; Anwar, A. P.; Imitiaz, M. S. *; Hafezali, I. H. (Emerald, 2020)
This paper reports findings on the effect of Economic Policy Uncertainty (EPU) in China on investment opportunities in five ASEAN countries. Upon employing multivariate DCC-GARCH tests along with Wavelet Coherence approach on monthly data from 2003 to 2019, we find the Malaysian stock market to be the least exposed to risks emanating from Chinese EPU, followed by Singapore, Philippines, Thailand, and Indonesia. Results for investment opportunities based on time horizon suggest that, for a short term holding period, investors are better off investing in Singapore and Indonesia, while, for medium term holding periods, all ASEAN markets appear lucrative except for the Philippines. Our findings contribute fresh insights into an emerging strand of literature focusing on the transmission of regional policy uncertainty into financial markets of economies with close economic, financial, and trade ties to China.